Subjective Health, Physical Activity, Body Image and School Wellbeing among Adolescents in South of Sweden - Ann-Christin Sollerhed; Emma Lilja; Emily Heldt Holmgren; Pernilla Garmy (Nursing Reports, 2021)
This study aimed to investigate subjective health and its associations with perceived body image (body appearance and body functioning), physical activity, perceived wellbeing in school, perceived family financial situation, and body mass index among 13- to 15-year-old boys and girls. The study was a cross-sectional study performed in four municipalities in Southern Sweden. Data were obtained from questionnaires completed by adolescents (median age 14; range: 13–15) in Sweden (n = 1518, 51% girls), with a participation rate of 73%. Body weight and body height were measured by school nurses and body mass index was calculated. Logistic regression analyses were carried out with subjective health as the dependent variable. Independent variables included in the model were perceived wellbeing in school, perceived family financial situation, perceived body image, physical activity, body mass index, sex, and residency. Variables significantly associated with good subjective health were good wellbeing in school, a perceived good family financial situation, perceived positive body appearance, perceived positive body functioning, being a boy, and high physical activity. Residency and body mass index were not associated with subjective health. Good subjective health is associated with good wellbeing in school, good family financial situation, positive body image, and high physical activity levels. The results highlight the importance of good school climates, the promotion of positive body image, and increased physical activity for adolescents.